Risk Management Strategies in Logistic and Supply Chain Operations - Betty Elizabeth Namwase (Uganda Christian University, 2023)
The study was conducted at Joint Medical Stores Headquarters in Nsambya, delved into risk management strategies within the realm of logistics and supply chain operations. The primary objectives were to assess the impact of risk identification, evaluate the role of risk mitigation and control, and investigate the relationship between risk assessment and analysis. Employing a descriptive research design, both qualitative and quantitative methods were utilized, including cross-sectional surveys and various sampling techniques. The findings of this study underscored the importance of effective communication and education in the context of risk management. They revealed a need for addressing uncertainties and concerns among respondents, particularly those who were Not sure or disagreed with certain statements. The study emphasized the significance of fostering a shared understanding and commitment to risk management practices within Joint Medical Stores, ultimately contributing to the efficiency and resilience of the supply chain. It suggested implementing enhanced training programs, comprehensive documentation, and integrated frameworks to improve risk management practices and their understanding among staff at all levels. In conclusion, this research provided valuable insights into risk management strategies within logistics and supply chain operations. It highlighted the need for better communication, education, and practical demonstrations to address concerns and uncertainties among stakeholders. By fostering a shared understanding and commitment to risk management practices, organizations like Joint Medical Stores could enhance their supply chain efficiency and resilience. The study's recommendations included training programs, comprehensive documentation, and integrated frameworks to improve risk management practices within the organization.
This is a dissertation.